2007
DOI: 10.1002/lt.21212
|View full text |Cite
|
Sign up to set email alerts
|

Biliary complications and outcomes of liver transplantation from donors after cardiac death

Abstract: Biliary complications after liver transplantation (LT) using organs retrieved from donors after cardiac death are not well characterized. The aim of this study was to evaluate the severity of biliary complications and outcomes after donation after cardiac death liver transplantation (DCD-LT). A retrospective evaluation of 20 DCD-LTs from 1997-2006 was performed. The recipient age was 53 Ϯ 8.7, and the donor age was 35 Ϯ 11 years. The warm ischemia time, cold ischemia time, peak alanine aminotransferase level, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
131
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(137 citation statements)
references
References 25 publications
5
131
1
Order By: Relevance
“…[15][16][17] Consistently, in a recent retrospective cohort analysis focusing on biliary complication after LT from DCD, cast formation occurred in 7 out of 20 cases (35%). 18 In that study, WIT was higher than in other reports. 15,16,19 Sample size bias may justify the lack of significance of cast prevalence in other similar studies.…”
Section: Inflammatory Picturecontrasting
confidence: 55%
“…[15][16][17] Consistently, in a recent retrospective cohort analysis focusing on biliary complication after LT from DCD, cast formation occurred in 7 out of 20 cases (35%). 18 In that study, WIT was higher than in other reports. 15,16,19 Sample size bias may justify the lack of significance of cast prevalence in other similar studies.…”
Section: Inflammatory Picturecontrasting
confidence: 55%
“…[19][20][21] A recent study from Johns Hopkins revealed the presence of biliary casts, proximal to ductal anastomotic strictures, in 35% of its NHBD liver transplants. 22 A possible reason that our current study did not show an increased incidence of BCS in NHBD grafts is the limited sample size. Our data set included only 6 patients (2 BCS and 4 controls) with NHBD grafts.…”
Section: Discussionmentioning
confidence: 63%
“…20,25,26,44 A single-center study showed an overall biliary complication rate of 50% for DCDs versus 28.3% for DBDs (P = .012) with biliary stricture rates of 46.7% and 26.5% (P = .018). 25 Croome and associates reported that 25% of DCD liver transplants developed biliary complications compared with 13% of DBD liver transplants (P = .062).…”
Section: Emre a Eren Et Al/experimental And Clinical Transplantationmentioning
confidence: 99%